Complex Refractive Index of Strontium Titanate in the Terahertz Frequency Range - V. R. Bilyk; K. A. Grishunin (Российский технологический журнал, 2019)
The recent progress in terahertz time-domain spectroscopy enables the accurate and reliable measurements of dielectric properties in comparison with the traditional far-infrared spectroscopy using an incoherent light source. The broadband THz-TDS is a powerful tool to determine the real and imaginary parts of a complex dielectric constant by the transmission which allows to detect the parameters of the soft modes in ferroelectrics. In this work, the terahertz time-domain spectroscopy was used to investigate the dependence of the complex refractive index of a single-crystal quantum paraelectric strontium titanate in the terahertz frequency range from 0.3 to 2 THz. It was shown that the low-frequency terahertz response of the material is determined by the soft phonon mode TO1. The measured experimental dependences showed a good agreement with the theoretical curves obtained from the analysis of the Lorentz oscillator model for the complex dielectric constant of strontium titanate. The obtained results are necessary for understanding the principle of possibility to manipulate the order parameter in ferroelectric materials and can be used to create energy-efficient memory devices with a speed of recording information close to the theoretical limit.